Wood smoke exposure of Portuguese wildland firefighters: DNA and oxidative damage evaluation. Issue 13 (3rd August 2017) - Abreu, Ana; Costa, Carla; Pinho e Silva, Susana; Morais, Simone; do Carmo Pereira, Maria; Fernandes, Adília; Moraes de Andrade, Vanessa; Teixeira, João Paulo; Costa, Solange
ABSTRACT: Portugal is among the European Union countries most devastated by forest fires each year. In the last three decades, more than 3.8 million hectares of forest were burned. Wildland firefighters are exposed to a variety of hazards, including many toxic combustion products that may lead to deleterious health effects. Epidemiological studies showed a positive association between firefighting and several chronic diseases, including cancer. Results from biomonitoring studies in firefighters, particularly concerning genotoxicity evaluation, constitute a valuable tool for investigating important occupational hazards. Thus, the aim of this study was to assess genotoxicity in a group of wildland firefighters using the comet assay for DNA damage and oxidative stress. Both parameters were increased in firefighters compared to controls, but significance was only found for basal DNA damage. No significant influence was found regarding major confounding variables on the genotoxic endpoints studied, with the exception of age. Data obtained provide preliminary information on human health effects of wildland firefighting exposure at genetic and molecular levels. These findings may also provide new important data to serve as public awareness to the potential adverse health risks involving wildland firefighting. Implementation of security and hygiene measures in this sector as well as good practices campaigns may be crucial to decrease risk.